(untitled) (Medical Forum Monthly, 2021)
Objective: To study the perceptions of medical students on online Physiology teaching-learning during COVID-19 pandemic and to evaluate the preference of medical students on online teaching, traditional teaching or both. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Jinnah Medical and Dental College, January to March 2021. Materials and Methods: The study participants included 62 MBBS 2nd year students. A questionnaire was distributed to each student. The questionnaire included 22 items regarding online teaching and online assessment. The medical students were asked to select a response for each item on the questionnaire including the preferred teaching method from online, traditional or both. The online recorded lectures were uploaded on student portal of JMDC website during COVID 19 pandemic period. The data was presented in terms of percentage for individual item, for preference in theory, practical, tutorial, assessment and the overall preferred teaching method. Results: The medical students were of the opinion that presence of teacher (74.2%), presence of colleagues (67.7%), asking the queries to teacher (71%) giving feedback to teacher (71%) were more important aspects for traditional teaching. Regarding the online recorded lectures getting enough time to understand the lecture (53.2%) and studying at own pace (54.8%) were found to be more important. In the preference of teaching method for theory (53.2%), practical (77.4%) tutorial (48.4%) and assessment (54.8%) the majority of students selected traditional method. The overall percentage of traditional method (56.5%) was higher as compared to online (27.4%) and both (16.1%). Conclusion: The majority of 2nd year medical students had a preference for traditional teaching methods in Physiology.